Implementasi Digital Marketing PT. Taman Wisata Candi Selama Pandemik Covid-19 - Khenresta, Tsanaa; Salasa, Yonaz; Oktaviani, Rani Chandra (Directorate of Academic Research and Community Services, 2021)
This study discusses how the implementation of the marketing communication strategy of PT. TWC on social media during the Covid-19 pandemic. This study aims to understand the marketing communication strategy of PT. TWC on social media and understand the tactics and alternative promos of PT. TWC during the Covid-19 pandemic. The research was conducted in a qualitative descriptive manner by conducting interviews with internal informants, external informants, and expert informants. In addition, literature review and observations were carried out. This study shows that there is a digitalization trend carried out by PT. TWC. In addition, PT. TWC is also using virtual tours as an alternative tactic to its marketing communication strategy Keywords: Covid-19 pandemic, social media, marketing communication strategy, virtual tour